Effectiveness of a theory-based back care intervention on spine-related behavior among pupils: a school-based randomised controlled trial (T-Bak study) - Zahra Akbari-Chehrehbargh; Sedigheh Sadat Tavafian; Ali Montazeri (BMC, 2020)
Abstract Background Children's health and welfare have a special place in research and policy in many countries. One of the most important concerns is the increasing rate of backache in children due to many of behavioral risk factors. The aim of this study was to evaluate the effectiveness of an educational program on promoting back-related behavior as well as knowledge, skills, beliefs, and self-efficacy among fifth grade girls. Methods The theory-based back care (T-Bak) study was a school-based randomised controlled trial (RCT) that assessed the effectiveness of developing a back care training program based on the social cognitive theory (SCT). A total of 104 schoolchildren aged 11 ± 1.0 years were assigned to intervention (n = 52) and control (n = 52) groups. The intervention group received six sessions training on proper lifting and carrying techniques, having proper posture during daily activities, and correct backpack wearing techniques with a 1-week interval while the control group received nothing. Then, the two groups were assessed for knowledge, skills, self-efficacy, beliefs, and behavior at four points in time: baseline, immediate, three and six-months post-intervention. The changes of the outcomes investigated using univariate repeated measures analysis of variance. Partial eta squared measure (ηp 2) was used to calculate effect sizes. Results A positive change was found for the intervention group back-related behavior from baseline to immediate post-intervention and follow-ups (F = 78.865, p < 0.001, ηp 2 = 0.22). Overall there were 36.4% improvement for knowledge (ηp 2 = 0.21), 53.2% for the skills (ηp 2 = 0.25), 19.5% for the self-efficacy (ηp 2 = 0.11), and 25.6% for the beliefs (ηp 2 = 0.14) scores from baseline to 6 months' follow-up assessments among the intervention group (p < 0.001). The results also showed a significant interaction effect between group and time. Conclusion The T-Bak intervention was effective in improving back-related behavior in pupils. It is now available and could be evaluated further in back-care related studies. Trial registration Current Controlled Trials IRCT20180528039885N1 , 30th Oct 2018, 'Prospectively registered'. https://www.irct.ir/trial/31534